Dietary Habits among Medical Science Students in Duhok City - Dilkhosh Shamal Ramadhan; Arazoo Issa Tahir; Rebar Yahya Abdullah (Hawler Medical University, 2021)
Background and objectives: Students at the university level are more exposed to changes in physical and social status and lifestyle changes, which will affect students' eating habits. This study aimed to assess dietary habits among medical science students in Duhok city. Methods: A descriptive cross-sectional study was conducted from 20th January 2019 to 28th April 2019. The cluster sampling procedure enrolled 359 medical science students aged 18-26 years from five medical science colleges in Duhok city. Dietary habits were obtained by direct interview. The questionnaire consists of three parts: socio-demographic characteristics, questions regarding main meals, and measuring dietary habits using a Likert scale. Data were analyzed using SPSS version 23. Results: Most of the study participants were males 56.8% with a mean age was 21 years. Slightly more than half of the students 52% claimed they ate three main meals every day and about 11% skipped it. About 45% of the participants ate breakfast every day. The most frequently eaten meals and beverages among students were soft drinks 80%, rice 80%, snacks 72%, and sweats/chocolate 70%. Decreased intake of fruits 60%, vegetables 50%, and dairy products 38% were observed. There were significant differences among males and females in food consumption and beverages namely, sports drinks, eggs, cheese, red meat, chips, and sweets/chocolate.  Conclusion: The current study indicated that skipping meals was typical among students. Most students had unhealthy food habits and behaviors according to the standard recommendations for eating and drinking daily. The assessment of dietary habits as a part of the health component can serve as a screening tool to identify adult students to improve their well-being and dietary habits.